Reflections on Teaching and Learning of Mathematics through Lesson Study and Video Critique - Iksan, Zanaton H.; Rahim, Marziah Bt Md. (Advances in Social Sciences Research Journal, 2017)
Teachers’ reflection is one important step in the implementation of Lesson Study. To enhance the professionalism of teachers, lesson study has become an important practice in the implementation of the Professional Learning Community (PLC) in Malaysia. “Video Critique” and “Lesson Study” are some of the tools in the implementation of PLC. As Lesson Study is newly introduced in 2011, teachers are still in the learning stage of implementing it. Among the problems teachers face is ways of making good reflections during classroom observation. Thus, this study aims to explore the ways in which excellent teachers reflect as well as their reflection level by looking at a video of teachers teaching at a school in Negeri Sembilan. The study was conducted using qualitative methods. The study participants were 17 excellent teachers, including two lecturers. Data was collected using reflective observations, documents of the participants, and recordings of the video critique sessions. Data was analysed using reflective dialogue session video documents analytical technique that has been transcribed. It was found that there are four stages of reflections: Descriptive, Dialogue Reflective, Descriptive Reflective and Critical Reflective. A majority of the excellent teachers reflected at the stage of Dialogue Reflective. Some of the excellent teachers made Descriptive Reflective, and only a few teachers succeeded brilliantly at Critical Reflective. Originality/value - This study implies a need for exposure to reflective practice during the process of observation so that teachers receive deep and meaningful feedback through practice in community learning.